Assement of the fluoride concentration and pH in different mouthrinses on the brazilian market - Delbem, Alberto Carlos Botazzo [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Castro, Alessandra Maia De [UNESP]; Pinto, Leila Maria Cesário Pereira [UNESP]; Bergamaschi, Maurício [UNESP] (Faculdade De Odontologia De Bauru - USP, 2003)
In this study, the fluoride concentration and pH of 14 commercial brands of mouthrinses were assessed in order to compare them with the values expressed on the labels and with those established by the National Sanitary Surveillance Agency. Forty-two (42) products were obtained from three places, with different manufacturing batches. The fluoride concentration was determined in diluted solutions, using a combined specific electrode for fluoride ion (9609 BN Orion Research) and ion analyzer (290 A Orion Research). The results showed that 50% of the solutions had statistically significant differences, with higher fluoride concentrations than those expressed on the labels, and the pH ranged from 4.23 to 7.34, but only one of the products registered the pH value on its label.

No presente estudo, o teor de flúor e o pH de 14 marcas comerciais de soluções para bochechos foram avaliados a fim de comparar com os valores expressos nos rótulos e com aqueles determinados pela Agência Nacional de Vigilância Sanitária. Foram adquiridos 42 produtos em três localidades, com diferentes lotes de fabricação. A concentração de flúor foi determinada em soluções diluídas, utilizando-se eletrodo específico combinado para íon flúor (9609 BN Orion Research) e analisador de íons (290 A Orion Research). Os resultados mostraram que 50% das soluções apresentaram diferenças estatisticamente significantes, com concentrações de flúor superiores àquelas expressas nos rótulos e o pH variou entre 4,23 a 7,34, mas apenas um dos produtos registrou o valor do pH em seu rótulo.
Avaliação do teor de flúor e pH em diferentes soluções para bochechos no mercado nacional
Keywords: Topical fluorides; Sodium fluoride; Dental caries; Fluoretos tópicos; Fluoreto de sódio; Cárie dentária